2015
DOI: 10.3389/fnbeh.2015.00075
|View full text |Cite|
|
Sign up to set email alerts
|

Acute administration of MK-801 in an animal model of psychosis in rats interferes with cognitively demanding forms of behavioral flexibility on a rotating arena

Abstract: Patients with schizophrenia often manifest deficits in behavioral flexibility. Non-competitive NMDA receptor antagonists such as MK-801 induce schizophrenia-like symptoms in rodents, including cognitive functions. Despite work exploring flexibility has been done employing behavioral paradigms with simple stimuli, much less is known about what kinds of flexibility are affected in an MK-801 model of schizophrenia-like behavior in the spatial domain. We used a rotating arena-based apparatus (Carousel) requiring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…Importantly, marked disruptions of behavioral functions similar to those found in schizophrenia can be induced in animal models using acute application of MK-801, a prototypical experimental high-affinity non-competitive antagonist of NMDA receptors. These include social deficits (low doses; Rung et al, 2005 ), cognitive deficits (low-to-moderate doses; van der Staay et al, 2011 ; Lobellova et al, 2013 , Kubík et al, 2014 ; Svoboda et al, 2015 ) and toxic and experimental psychoses (higher doses, Vales et al, 2006 ; Lobellová et al, 2015 ). Chronic experiments aimed at mimicking the neurodevelopmental abnormalities have shown that these manipulations can also induce schizophrenia-like behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, marked disruptions of behavioral functions similar to those found in schizophrenia can be induced in animal models using acute application of MK-801, a prototypical experimental high-affinity non-competitive antagonist of NMDA receptors. These include social deficits (low doses; Rung et al, 2005 ), cognitive deficits (low-to-moderate doses; van der Staay et al, 2011 ; Lobellova et al, 2013 , Kubík et al, 2014 ; Svoboda et al, 2015 ) and toxic and experimental psychoses (higher doses, Vales et al, 2006 ; Lobellová et al, 2015 ). Chronic experiments aimed at mimicking the neurodevelopmental abnormalities have shown that these manipulations can also induce schizophrenia-like behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of investigators have examined the role of the NMDAR, as well as other glutamate receptors and transporters (Karlsson et al, 2009, Barkus et al, 2012), in reversal learning and other forms of cognitive flexibility (for review, see (Jentsch and Roth, 1999). This work has led to reports that acute, systemic NMDAR blockade (with MK-801) can cause impairments in spatial reversal learning (Lobellova et al, 2013), but also fail to affect reversal performance and instead disrupt set-shifting (Svoboda et al, 2015). The literature on the effects of subchronic NMDAR antagonism with phencyclidine (PCP) (considered a potential model of schizophrenia (Brigman et al, 2010a) is also equivocal.…”
Section: Neurochemical Modulation Of Reversalmentioning
confidence: 99%
“…MK-801, or dizocilpine, a N-methyl-D-aspartate receptor (NM-DAR) antagonist, was first used as a pharmacologic model of psychosis in rats in 1999 [6] and is still widely utilized as a model for symptoms observed in schizophrenia. MK-801 may not be able to model schizophrenia in its entirety but it can mimic particular cognitive deficits such as behavioral inflexibility [7], impaired spatial memory (reviewed in [8]), and social withdrawal [9]. However, the use of MK-801 as a pharmacological model should not be limited to the symptoms of schizophrenia, considering the complexity and the multiple overlapping domains of neuropsychiatric disorders in humans [10,11].…”
Section: Introductionmentioning
confidence: 99%